Influence of indoor microclimate distribution on mould infestation in a university library - Ali, Maisarah; Oladokun, Majeed; Osman, Samsul Bahrin; Samsuddin, Niza; Hamzah, Hairul Aini; Salleh, Md. Noor (2014)
Indoor mould contamination portends grave consequence to the stored components as well as inhabitants of infested dwellings. Such defilement, which is due to favourable growth environment for micro-organisms, is often associated with Sick Building Syndrome (SBS) and other Building Related Illness (BRI). As the economic development of Malaysia continues, increase numbers of air-tight, fully air conditioned buildings are evolving. Currently limited guidelines exists on Indoor Air Quality (IAQ) in Malaysia and its knowledge amongst the public is lacking. Hence, diagnosing the aggravating factors favouring indoor mould becomes beneficial as earlier detection is often difficult until growth has advanced. The study aimed at investigating mould infestation in a mechanically ventilated library building in Malaysia. Microclimate parameter and mould sampling were carried out. The microbial investigation results in 72 isolates whose distribution were 86% mould, 13% yeast and 1% bacterial. It is found that Aspegillus sp. and Onychocola sp. were most common. The library internal microclimate distribution is characterised by uneven hygrothermal profile which results in high level of cellulolytic mould species that are highly detrimental to books and other archival materials. It is recommended that the HVAC system operations and set-points be critiqued to bring the ambient to the preservation requirements. In addition, load balancing for thermal and hygric distribution analysis should be executed to eliminate dead-spots in temperature and moisture distributions. Keywords—mould contamination; microbial assessment; indoor microclimatic parameters; hygrothermal profile; indoor air quality, time-series data